The Jinnah Mosque, St. Joseph, Trinidad, B.W.I. - Fung, Arthur, C. (Arthur C. Fung, 2010)
Photo of mosque in St. Joseph, Trinidad and Tobago. "A beautiful monumental structure erected by the Trinidad Muslim League by public subscription in memory of the founder of Pakistan, Quaid-i-Azam Mohammed Ali Jinnah (Opened April 25th, 1954)" Letter. 15 C "Ned Antillen" stamp.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Mosques--Trinidad and Tobago; Church buildings--Trinidad and Tobago; Islam--Trinidad and Tobago; Muslims--Trinidad and Tobago; Architecture--Trinidad and Tobago; Islam and architecture--Trinidad and Tobago